Risk of Profit Loss Sharing Financing: The Case of Indonesia - Ernawati, Ernawati (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This study analyzes the risk of profit-and-loss sharing finance in IndonesianIslamic banking. Data used is secondary data obtained from the Financial ServicesAuthority’s 2009-2014 publication. Financing risk is measured by risk returnand opportunity cost. Results of the study show that risk return in mudharabafinancing is more volatile than that in musharaka as it is potentially driven byagency problems. In all groups of banks, higher incomes are more promising inmudharaba than musharaka; but individually musharaka is more attractiveto Islamic Rural Bank groups, and vice versa for the Sharia Bank groups. Theone side it is more secure for Islamic banking to allocate funds in musharakacontract, which is an alternative to murabaha. However, musharaka contractis less attractive due to lower potential returns. Although high returns are morepromising in mudaraba, this financing mode has higher risk of returnsDOI: 10.15408/aiq.v8i1.2511